Innovative Paths to Character: Online Learning's Role in Instilling Independence and Responsibility in Islamic Education - Sadam Fajar Shodiq (At-Ta'dib, 2023)
Every youth in the digital world must exhibit the attributes of independence and responsibility. Equipped with the qualities of autonomy and accountability, youngsters residing in the digital age will possess the ability to endure. The objective of this study is to ascertain the impact of online learning on the assimilation of the qualities of self-reliance and accountability among high school (SMA) students. This study employed a quantitative methodology utilizing random sampling procedures. A total of 179 students were included in the sample. The data were gathered through the use of a questionnaire and examined using a basic linear regression analysis. The findings indicate a substantial impact of 47.9% of online learning on the acquisition of independence and 31% on the development of responsibility. The qualities of autonomy and accountability can be absorbed through the process of habituation and the influence of exemplary educators, both within and outside the confines of the classroom. The study's findings emphasize the necessity of a comprehensive approach to education in the digital age, recognizing the substantial influence of online learning on the development of students' personality. By considering these consequences, it is possible to develop purposeful and efficient character education approaches in the changing realm of digital education.